2008
DOI: 10.1590/s0034-89102008000400020
|View full text |Cite
|
Sign up to set email alerts
|

Inquérito sobre uso de medicamentos por idosos aposentados, Belo Horizonte,MG

Abstract: OBJECTIVE:To describe self-reported use of medicines by Brazilian elderly retirees focusing on gender differences. METHODS:Household survey conducted in a random sample comprising 667 subjects aged 60 years or more who were living in Belo Horizonte, Southeastern Brazil, in 2003. The elderly were interviewed by pharmacists, using a standardized questionnaire. The prevalence of medicine use and mean use in the 15 days previous to the interview were estimated and then stratifi ed by gender according to sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
39

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 15 publications
1
8
0
39
Order By: Relevance
“…In the current study, the most widely used drug classes (cardiovascular, nervous system, alimentary tract and metabolism, blood and blood forming organs, and musculoskeletal system) reproduce a consumption pattern observed in elderly populations in different countries 13,14 and in Brazil 15,16 . The use of these drug classes relates to treatment and prevention of typical health events for this phase of life, like hypertension, coronary disease, diabetes, and chronic pain.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In the current study, the most widely used drug classes (cardiovascular, nervous system, alimentary tract and metabolism, blood and blood forming organs, and musculoskeletal system) reproduce a consumption pattern observed in elderly populations in different countries 13,14 and in Brazil 15,16 . The use of these drug classes relates to treatment and prevention of typical health events for this phase of life, like hypertension, coronary disease, diabetes, and chronic pain.…”
Section: Discussionmentioning
confidence: 72%
“…Studies in other countries 12,13,14 and in Brazil 15,16 have identified drugs for the cardiovascular system, central nervous system, metabolism, and alimentary tract as the most frequently consumed among the elderly. More recently, changes in the pattern of use of some drug classes have been observed in some populations, especially in the pattern of consumption of drugs for hypertension 17,18 , as well as an increase in the use of lipid modifying 5,17 , psychoactive 19,20 , and antiepileptic drugs 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Verificou-se que 257 (88%) utilizavam medicamentos prescritos, principalmente para o controle da hipertensão arterial. Esse dado é semelhante ao encontrado em um estudo realizado no Nordeste do Brasil, no qual 80,3% dos idosos da área central faziam uso de pelo menos um medicamento prescrito (Coelho Filho et al, 2004) e de outro estudo em Belo Horizonte onde a prevalência do uso de medicamentos foi de 90,1% (Ribeiro et al, 2008 (Gama & Silva, 2006). Em um hospital geriátrico em Brasília houve uma prevalência de 83,9% de pacientes em uso da fitoterapia (Pereira, 2008).…”
Section: Resultsunclassified
“…Esses dados estão de acordo com estudos prévios sobre envelhecimento. 26,27 A presença de algumas doenças e o uso de múltiplos medicamentos são considerados fatores de risco para ocorrência de quedas em idosos. 28,29 Neste estudo, 43,4% dos idosos usavam quatro ou mais medicamentos regularmente, indicando que uma parte importante da amostra encontra-se com risco aumentado de cair.…”
Section: Procedimentos De Coletaunclassified